Öğretmen Adaylarının Matematik Öğretmeye Yönelik Kaygı Düzeylerinin İncelenmesi - TATAR, Enver; ZENGİN, Yılmaz; KAĞIZMANLI, Türkan Berrin (My University, 2016)
Bu araştırma, matematik öğretmeni adaylarının matematik öğretme kaygı düzeylerini belirlemek amacıyla yapılmıştır. Araştırmada nicel araştırma yaklaşımlarından tarama yöntemi kullanılmıştır. Araştırma Türkiye’de bulunan bir üniversitenin eğitim fakültesindeki 475 matematik öğretmeni adayı ile gerçekleştirilmiştir. Veri toplama aracı olarak kişisel bilgi formu ve matematik öğretmeye yönelik kaygı ölçeği kullanılmıştır. Ölçek; alan bilgisi, öz güven, matematiği öğretmeye yönelik tutum ve alan eğitimi bilgisinden kaynaklanan öğretme kaygısı olmak üzere 4 alt boyuttan oluşmuştur. Araştırma sonucunda, öğretmen adaylarının matematiği öğretmeye yönelik kaygı düzeylerinin ortalama puan değerinin altında olduğu belirlenmiştir. Öğretmen adaylarının matematiği öğretmeye yönelik kaygı düzeylerinde; öğrenim görülen lisans programına göre alan bilgisi alt boyutu ve genel kaygıları açısından fark olduğu tespit edilmiştir. Ayrıca matematik öğretmeni adaylarının matematiği öğretmeye yönelik kaygılarında alan eğitimi bilgisi alt boyutu açısından sınıf düzeyine göre fark olduğu görülmüştür. Son olarak öğretmen adaylarının matematiği öğretmeye yönelik kaygılarının cinsiyete göre farklılık göstermediği belirlenmiştir.
Examining Levels of Mathematics Teaching Anxiety of Pre-service Teachers
This research was conducted in order to determine the levels of mathematics teaching anxiety of pre-service mathematics teachers. Survey design was used in the research. The sample of the research was composed of 475 pre-service mathematics teachers who study in the education faculty in a state university in Turkey. A personal information form and a mathematics teaching anxiety scale were used as a data collection tools in the research. The scale comprises 4 sub-dimensions: teaching anxiety caused by content knowledge, teaching anxiety caused by self-confidence, teaching anxiety caused by attitude towards teaching mathematics and teaching anxiety caused by teaching knowledge. As a result of the research, it was determined that the levels of mathematics teaching anxiety of pre-service teachers are below the average score value. Accordingly, it was detected that there was a difference among the levels of mathematics teaching anxiety of pre-service teachers in terms of teaching anxiety caused by content knowledge sub-dimension and their general anxiety according to elementary undergraduate program and secondary undergraduate program. Moreover, it was observed that there was a difference according to class levels among the mathematics teaching anxiety of pre-service mathematics teachers’ mathematics teaching anxiety in terms of the sub-dimension of teaching knowledge. Lastly, it was determined that the anxiety of mathematics teaching of pre-service teachers did not differ in terms of gender.
Keywords: matematik öğretme kaygısı, matematik öğretimi, kaygı, matematik öğretmeni adayı